Penerapan Personal Branding Andini Shidqin Maza sebagai Beauty Influencer Palembang di Media Sosial Tiktok - Delima Destiana Firmansyah; Isna Wijayani (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
The existence of TikTok social media has created a new phenomenon among youth. An influencer is also known as someone who has the ability to influence other people in making decisions to buy a product. TikTok influencers are people who are famous for having a fairly high popularity, namely by having a large number of followers, which is tens to hundreds of thousands. Someone is said to be an influencer because of the large number of followers or fans on TikTok and this can also be seen from the interesting video content that is liked by other TikTok users. Influencers use TikTok to build their personal brand according to their skills and interests. Based on gender, influencers are divided into several types, namely travel influencers, fashion influencers, food influencers, lifestyle/socialite influencers, comedy influencers, and beauty influencers. TikTok @andinishidqin05 has around 56.4K followers and 1.8 million likes (as of July 14, 2022). The author sees Andini Shidqin Maza has something interesting as an influencer. It can be seen from his who has 56.4 thousand followers and can form good personal branding on TikTok so that he can attract the attention of several big brands in Indonesia to use his services as endorsers. Keywords: Personal Branding, Social Media TikTok, Beauty Influencer